First offensive shot in elite table tennis - Fuchs, M.; Lames, M. (International Journal of Racket Sports Science, 2021)
At the (very) first shots in table tennis, players face a basic tactical decision: either return the ball short and passively or attack it with an offensive shot. In the first case, there is lower risk but no pressure for making the point, in the second case pressure is created, but at the cost of high risk, because the serve and other prior "passive" shots try to make an offensive shot as difficult as possible, typically being short and flat. Thus, the real turntable of a rally is this shot - in this study called "first offensive shot" (FOS) - which is the transition from passive to offensive play.